On symmetric dual models associated with multiple cost control problems - Savin Treanţă; Virgil Ionică; Guoju Ye; Wei Liu (Archives of Control Sciences)
In this paper, we build a symmetric dual model associated with a family of multiple cost control problems. More concretely, under weaker generalized convexity hypotheses than those formulated in previous research works (for classical multiobjective variational problems), we establish and extend the framework to controlled variational models, and, therefore, the derived results become significantly stronger and more generous than those presented so far in the specialized literature.